(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
The purpose of this work is to investigate how members of a psychotherapeutic group experience and understand the phenomenon of self-disclosure, what is a conception of the self-disclosure and what is the dynamics of the process of self-disclosure in a psychotherapy group. The phenomenon of self-disclosure was investigated in three psychotherapeutic groups of existential experience. In the introductory part of this work, the concept of self-disclosure is defined, and the psychotherapy group is presented as a part of the broader context of interpersonal relationships. The types of self-disclosure are listed and the features of self-disclosure in therapeutic groups of existential experience are analysed. The method of focus groups was used in this research. Focus group interviews were conducted according to the focus group work schedule prepared in advance. The participants of the focus groups were questioned about their experience of self-disclosure in a psychotherapeutic group. 23 persons – 4 men and 19 women took part in 3 focus groups. The researchers moderated the focus groups. The duration of discussions in the focus groups was about 1,5-2 hours, the whole process was audio- and videotaped. The original texts of the focus group discussions were obtained by transcribing audio records. The analysis of the phenomenon was performed on the basis of the written texts, which included 4 stages: (1) the formulation of summary statements; (2) the organization of summary statements; (3) the comparison of summary statements and the formulation of the descriptions of the structural parts of the phenomenon; (4) the formulation of the final description. The result of this process is a detailed description of the phenomenon of self-disclosure in a psychotherapy group, which consists of 3 parts – experiences before, at the time and after the self-disclosure. The description also reflects the experiences of factors that facilitate or block self-disclosure in a group. The final description not only conforms, but also broadens and significantly complements the assumptions of the introductory part.